(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
A research was conducted to determine the dietary inclusion levels of sunflower ((Helianthus annus) oil (SWO) on the growth performance of broiler chickens. One hundred and fifty four- weeks old broiler chickens were randomly allotted into 5 treatments with three replicates consisting of 10 birds each in a completely randomized design (CRD). Birds in T2, T3, and T4 and T5 were fed the basal diet mixed with 100, 200, 300, and 400 mg/kg of sunflower oil, while birds in T1 were fed the basal diet and Neomycin at 2.0 g/kg. The experiment lasted for 28 days. Feed and clean water were offered ad libitum and all other management practices were strictly observed throughout the experimental period. Data were collected on average weight gain (AWG), total feed intake (TFI), and feed conversion ratio (FCR). Data generated was analyzed using analysis of variance (ANOVA) using SPSS. Phytochemical composition of sunflower oil revealed the presence of bioactive chemicals like Flavonoids (10.06 %), tannins (6.96 %), phenols (7.06 %), trepenoids (5.01 %), steroids (4.47 %), alkaloids (3.86 %) and saponins (4.47 %). Results of the growth performance showed that birds fed sunflower oil had significantly (P<0.05) higher final body weight, average body weight gain, total feed intake and better feed conversion ratio compared to the control given synthetic antibiotics (T1). Mortality was only recorded among birds in T1 and none was recorded in the other treatments (P<0.05). It can be concluded that the inclusion of sunflower oil up to 400 mg/kg in the diets of broiler chickens enhanced growth performance and suppressed the activities of pathogenic microorganisms.